'No, we vote for whoever we want to': young British Muslims making new claims on citizenship amidst ongoing forms of marginalisation. (9th August 2021) - Manning, Nathan; Akhtar, Parveen
ABSTRACT: Young people's relationship with politics is routinely deemed problematic by a range of influential actors. Amidst concerns over disengagement and the potential for radicalisation, the political participation of Muslim young people is often particularly scrutinised. In contrast to such 'crisis narratives', this paper reports on qualitative research with young Muslims in a northern English city. Consistent with research on young people in general, the findings reveal widespread disillusionment with electoral politics amongst this group. Despite this, most respondents were politically engaged and voiced claims for a substantive representation which addressed mainstream and often national political issues. These claims were articulated in contrast to an older generation who were seen as prioritising local issues and representation much more closely tied to kinship and ethnic identity. These Muslim young people were asserting claims for a more mainstream citizenship marked against the political and cultural orientations of an older migrant generation and a wider social context of ongoing racism, Islamophobia and marginalisation.